2019
DOI: 10.1121/1.5092608
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of greatest temporary hearing threshold shift in harbor seals (Phoca vitulina) depends on fatiguing sound level

Abstract: Harbor seals may suffer hearing loss due to intense sounds. After exposure for 60 min to a continuous 6.5 kHz tone at sound pressure levels of 123-159 dB re 1 mPa, resulting in sound exposure levels (SELs) of 159-195 dB re 1 lPa 2 s, temporary threshold shifts (TTSs) in two harbor seals were quantified at the center frequency of the fatiguing sound (6.5 kHz) and at 0.5 and 1.0 octaves above that frequency (9.2 and 13.0 kHz) by means of a psychoacoustic technique. Taking into account the different timing of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…For most of the fatiguing sound center frequencies tested with these California sea lions for this research project, a similar pattern was observed, though in most cases the greatest TTS occurred at half an octave above the center frequency (Cody & Johnstone, 1981;Kastelein et al, 2021bKastelein et al, , 2022aKastelein et al, , 2022b; in the present study, it occurred at the center frequency (only 1.4 dB higher than the maximum TTS measured with the hearing test frequency half an octave above the center frequency of the fatiguing sound). The hearing frequency most affected depends not only on the frequency, but also on the SEL of the fatiguing sound (Kastelein et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For most of the fatiguing sound center frequencies tested with these California sea lions for this research project, a similar pattern was observed, though in most cases the greatest TTS occurred at half an octave above the center frequency (Cody & Johnstone, 1981;Kastelein et al, 2021bKastelein et al, , 2022aKastelein et al, , 2022b; in the present study, it occurred at the center frequency (only 1.4 dB higher than the maximum TTS measured with the hearing test frequency half an octave above the center frequency of the fatiguing sound). The hearing frequency most affected depends not only on the frequency, but also on the SEL of the fatiguing sound (Kastelein et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring is needed for harbor porpoises, which are protected throughout their range, to better understand the driving factors for entering rivers. This possible barrier with a TTS potential should also be addressed for harbor seals, since these animals also occur in this area (Taupp, 2019) and are capable of hearing the acoustic flowmeter signal (Kastelein et al, 2009a;Kastelein et al, 2019b). Seals may also suffer from habitat exclusion by the acoustic signals of the flowmeter as acoustic signals with a 28 kHz component are even used for deterring seals (Kastelein et al, 2015b).…”
Section: Effects On Behaviormentioning
confidence: 99%
“…Measurements of the auditory systems of harbour seals have noted that their highest underwater hearing sensitivity occurs between 50 Hz and 86 kHz (Mohl, 1968; Terhune, 1988; Kastelein et al, 2009a; Kastelein et al, 2009b; Cunningham & Reichmuth, 2016), encompassing the frequency ranges at which the majority of ADDs operate (0.5–40 kHz) (Lepper et al, 2014; Todd et al, 2021). A number of captive studies have documented both TTS and PTS from exposures to noise between these frequencies (0.5–40 kHz) (Kastak et al, 2005; Kastelein et al, 2012; Kastelein et al, 2013b; Kastelein, Helder‐Hoek & Gransier, 2019; Reichmuth et al, 2019; Kastelein et al, 2020a; Kastelein et al, 2020b). However, although models have predicted this noise source as a risk of auditory impairment to seals (Götz & Janik, 2013; Lepper et al, 2014), the potential for auditory impairment in non‐target seals at sea and in waters around protected sites has yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%